ナンキョク エンコ スイチュウ ノ ユウキ タンソ オヨビ シボウサン ノ ソクテイ - 松本, 源喜; マツモト, ゲンキ; 半谷, 高久; ハンヤ, タカヒサ; MATSUMOTO, Genki; HANYA, Takahisa (国立極地研究所, 1977)
P(論文) 南極ドライバレーのパンダ湖,ポニー湖およびフリクセル湖の底層水中の全有機炭素(TOC),酢酸エチル抽出有機炭素(EOC)および脂肪酸の測定を行った.その結果,高濃度のTOC (18.6-63.8 mg/l))およびEOC (3.8-9.1 mg/l)が測定された.脂肪酸は不飽和のC_<16:1>(炭素数:不飽和数)とC_<18 : 1>を含むC_<8:0>からC_<32:0>の範囲のものが同定された.それらの全濃度は2.8-19μg/lである.また,ポニー湖からはフェニル酢酸が同定された.これらの有機化合物は主として湖水中の藻類,バクテリアおよび菌類などの微生物に由来するものと思われる. Total organic carbon (TOC), extractable organic carbon (EOC), and fatty acids were determined in bottom waters of Lakes, Vanda, Bonney, and Fryxell in the Dry Valleys of Victoria Land, Antarctica. The high concentrations of TOC and EOC were found, ranging from 18.6 to 63.8 mg/l and from 3.8 to 9.1 mg/l respectively. Fatty acids ranging from C_<8:0> (carbon numbers: numbers of unsaturation) to C_<32:0> including C_<16:1> and C_<18:1> were determined by using a combined gas chromatograph-mass spectrometer (GC-MS), and their total concentrations were 2.8-19μg/l. Furthermore, phenylacetic acid was identified in the bottom waters of Lake Bonney. The sources of those organic compounds may be due to the lake organisms, such as algae, bacteria, and fungi. departmental bulletin paper